(untitled) (Journal of Global Humanities and Social Sciences, 2025)
The global technological competition landscape is undergoing profound adjustments, and China’s economy is transitioning from factor-driven to innovation-driven growth, with traditional development models facing bottlenecks. Core concepts in Schumpeter’s innovation theory—such as “new combinations of production factors” and “creative destruction”—provide crucial theoretical support for addressing China’s challenges of insufficient innovation coordination and sluggish momentum conversion. This paper systematically examines the core tenets and theoretical characteristics of Schumpeter’s innovation theory. By integrating the implementation status and practical challenges of China’s innovation-driven development strategy, it explores the theory’s implications for deepening the strategy across dimensions such as nurturing innovation entities, optimizing factor allocation, and improving the institutional environment. This analysis provides theoretical references and practical pathways for China to overcome innovation bottlenecks, establish an independent innovation system, and achieve high-quality development.